Citrate-functionalized hydroxyapatite nanoparticles for pH-responsive drug delivery. Issue 81 (16th August 2016) - Verma, Gunjan; Barick, K. C.; Shetake, Neena G.; Pandey, B. N.; Hassan, P. A.
Abstract : Development of biocompatible citrate-functionalized hydroxyapatite nanoparticles for pH responsive delivery of doxorubicin. Abstract : The design and fabrication of multifunctional nanocarriers that can trigger the release of drugs with external stimuli such as pH, temperature is gaining increasing importance, and shows promising potential for clinical applications. This study demonstrates the synthesis of citrate-functionalized hydroxyapatite nanoparticles (Cit-HANPs) using a co-precipitation method and its in situ surface modification for drug delivery applications. The surface modification of nanoparticles with citric acid was evident from infrared spectroscopy, thermal analysis and zeta potential measurements. The nitrogen adsorption–desorption isotherm reveals formation of mesoporous Cit-HANPs with a large surface area of 182.9 m 2 g −1 . The anticancer drug, doxorubicin hydrochloride (DOX) was used as a model drug to evaluate the potential use of Cit-HANPs in drug delivery. The complexation of positively charged DOX to Cit-HANPs was apparent from the UV-visible spectroscopy. A loading efficiency of ∼85% (w/w) was observed with a drug to particle ratio of 1 : 10 and the loaded drug showed a pH dependent sustained release behaviour. The high drug loading capacity of Cit-HANPs has been attributed to the electrostatic binding of the positively charged drug to the negatively charged Cit-HANPs as well as their porous nature. The cell viability and hemolysis assay suggests that Cit-HANPs have insignificant toxicity. Furthermore, the cellular internalization capability of these citrate functionalized nanoparticles was substantiated by fluorescence microscopy studies.